OVARIAN APOPLEXY: CURRENT CONCEPTS OF PATHOGENESIS, DIAGNOSIS, AND TREATMENT - Narzikulovna, Marzhona (Uzbekistan Open Conference, 2025)
Ovarian apoplexy is an acute gynecological condition characterized by a sudden rupture of ovarian tissue with intra-abdominal bleeding. It is one of the leading causes of acute abdomen in women of reproductive age. Modern research reveals a multifactorial pathogenesis involving vascular, endocrine, and mechanical components. This article presents current insights into the pathogenesis, clinical manifestations, instrumental diagnosis, and treatment strategies of ovarian apoplexy. Special attention is given to management approaches based on the extent of hemorrhage and reproductive intentions of patients.
Keywords: ovarian apoplexy; internal bleeding; ovulation; laparoscopy; acute abdomen